On a class of analytic multivalent functions involving generalized Bernardi-Libera - Livingston integral operator - Mahmood, Zainab H.; Rasheed, Reem O.; Jassim, Kassim A. (Iraqi Journal of Science, 2026)
In this paper, a class of analytic and multivalent functions and its various properties is introduced, by using Generalized Bernardi-Libera-Livingston of Integral Operator which is defined on the open unite disk U. Coefficient bounds, distortion theorem, closure and radii of star likeness, convexity are obtained.